Advances in nanomaterials for photodynamic therapy applications: Status and challenges. (April 2020) - Chen, Jianming; Fan, Taojian; Xie, Zhongjian; Zeng, Qiqiao; Xue, Ping; Zheng, Tingting; Chen, Yun; Luo, Xiaoling; Zhang, Han
Abstract: Photodynamic therapy (PDT), as a non-invasive therapeutic modality that is alternative to radiotherapy and chemotherapy, is extensively investigated for cancer treatments. Although conventional organic photosensitizers (PSs) are still widely used and have achieved great progresses in PDT, the disadvantages such as hydrophobicity, poor stability within PDT environment and low cell/tissue specificity largely limit their clinical applications. Consequently, nano-agents with promising physicochemical and optical properties have emerged as an attractive alternative to overcome these drawbacks of traditional PSs. Herein, the up-to-date advances in the fabrication and fascinating applications of various nanomaterials in PDT have been summarized, including various types of nanoparticles, carbon-based nanomaterials, and two-dimensional nanomaterials, etc. In addition, the current challenges for the clinical use of PDT, and the corresponding strategies to address these issues, as well as future perspectives on further improvement of PDT have also been discussed.